Experimental Study of Cracked Knee of Frame - Rossmanith, H.P.; Beer, R.J. (Engineering Transactions, 1983)
Fracture mechanics and photoelastic methods are utilized to determine correction functions for stress intensity factors for cracked knees of frame. A simple engineering method of analysis is demonstrated.